BSE enterprise network system - Amir, Azman (2014)
Dealer and Admin is the important role in BSE Enterprise Network System. BSE Enterprise Network is a company that selling reload products in Malaysia for example Maxis, Celcom and Digi. Current method is they are using SMS as a platform for deposit system. Dealers will bank in to admin, and admin will verify the payment and insert the deposit into dealer's account. If there is any third scamming issues from dealers, then really hard to trace back because there is no deposit history to be check. A proper management system is needed to solve those problems. The objectives of this system are: (1) To develop a prototype information website for BSE Enterprise Network, (2) To develop BSE Enterprise Network Management for dealer and admin, (3) To notify dealer about information status by SMS. By the use of this system, admin can easily check back deposit and transaction history by dealers before. Besides, dealers also can see their transaction and deposit progress. The system has been developed and it shows all of the objectives can be achieved according to user testing that has been conducted before. Hence, this system should undergo future enhancement so that all users of BSE Enterprise Network can use this system for the ease of the system management.